2020
DOI: 10.1007/978-3-030-46224-6_6
|View full text |Cite
|
Sign up to set email alerts
|

To Click or Not to Click? Deciding to Trust or Distrust Phishing Emails

Abstract: While the email traffic is growing around the world, such questions often arise to recipients: to click or not to click? Should I trust or should I distrust? When interacting with computers or digital artefacts, individuals try to replicate interpersonal trust and distrust mechanisms in order to calibrate their trust. Such mechanisms rely on the ways individuals interpret and understand information. Technical information systems security solutions may reduce external and technical threats; yet the academic lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…In this section, we first describe the experimental protocol we used to conduct a study with 249 participants on how they interpreted phishing emails, and then decided to trust or distrust them. Second, we discuss the results that were already partially presented by Arduin (2020) during the EWG‐DSS sixth$\text{sixth}$ ICDSST 2020 “Cognitive Decision Support Systems and Technologies” held by the Faculty of Economics and Business, Zaragoza, Spain. Third, we present some examples of “trust‐optimized” phishing emails and discuss the limits and ethical implications of this research.…”
Section: Research Proposal and Experimental Protocolmentioning
confidence: 99%
“…In this section, we first describe the experimental protocol we used to conduct a study with 249 participants on how they interpreted phishing emails, and then decided to trust or distrust them. Second, we discuss the results that were already partially presented by Arduin (2020) during the EWG‐DSS sixth$\text{sixth}$ ICDSST 2020 “Cognitive Decision Support Systems and Technologies” held by the Faculty of Economics and Business, Zaragoza, Spain. Third, we present some examples of “trust‐optimized” phishing emails and discuss the limits and ethical implications of this research.…”
Section: Research Proposal and Experimental Protocolmentioning
confidence: 99%
“…Knowledge can be categorized into explicit and implicit knowledge. Explicit knowledge is usually gained through S Tian and Jensen [53] S Arduin [54] M learning and direct training, whereas implicit knowledge is gained from experiences, especially after encountering phishing attacks. Studies have found that, the more individuals are familiar with computers and technology, the more capable individuals would be in coping with phishing emails [57].…”
Section: A Stage One: Long-term Stablementioning
confidence: 99%